Study on Clinical Presentation of Breast Carcinoma of 50 Cases - Mira Pervin, Mosammat; Deb Nath, Haradhan; Mejbahul Bahar, Mohd.; Alam, Ashraful; Bhowmik, Juthi (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Breast cancer results from uncontrolled proliferation of malignant cells resulting appearance of a lump or a mass in the breast. Although many epidemiological risk factors have been identified, the cause of any individual breast cancer is most often unknowable. A womens reaction to any suspected disease of breast may include fear of disfigurement, loss of sexual attractiveness and death. Social and religious factors, unawareness of fatality of the disease, fear of infertility hinder early diagnosis & treatment. Early diagnosis is the key to increased survival. Objective: To find out clinical presentation for breast cancer. Study design: It is a prospective study of 50 carcinoma breast patients who palpable breast lump. It was conducted during the six months period. Data were collected pre-designed data collection sheet. Data were analysis statistical package for social science (SPSS) program. Result: Most of the malignant lesions are above the age of 40 years and peak incidence are between 41-50 years and most of patients under this study were in advanced stage-III (54%) and stage-IV (22%). Patients were presented as nipple discharge (20%), pain in the breast (26%), ulceration over the lump (14%), paeud orange (10%) skin fixation over the lump (18%), fixation to the chest wall (14%) nipple retraction (22%). Among the 50 patients there was only one male ca-breast patient (2%). Among the histopathological types infiltrating duct cell carcinoma (NST) were 41 (82%), ductal carcinoma in situ 6 (12%), lobular carcinoma invasive 2 (4%), lobular carcinoma in situ 1 (2%) and carcinoma involved in different quadrants were upper & outer 21 (42%), lower outer 5 (10%), upper and inner 12 (24%), lower and inner 4 (8%), central 7 (14%) and breast as a whole involvement was 1 (2%). About the involvement of carcinoma breast, left breast involvement were 52%, right breast 46% and bilateral involvement was 2%. Conclusion: This prospective study shows an alarming high incidence of carcinoma breast with palpable breast lump. The diversity of clinical presentation of breast lumps in different age group were observed is our hospital practice. This study gives an idea about the incidence of various types of lesions of breast in different age groups in our country. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21048